1968
DOI: 10.1002/jsfa.2740191206
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in oats : Glyceryl esters of caffeic and ferulic acids

Abstract: Of the antioxidants extracted from oats, 36% (by weight) consists of six compounds which are more strongly adsorbed on to silicic acid than those previously described,1.2 One of these has been isolated by column chromatography. On hydrolysis it yields caffeic acid (2 moles), ferullc acid (1 mole), glycerol mole) and long-chain o-hydroxyacid (1 mole). The w-hydroxyacid fraction contains the homologues, 8 2 2 (5 %), c 2 6 (64 %), and Czs (31 %).The probable structures of the compounds are discussed. Introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1977
1977
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 5 publications
1
20
0
1
Order By: Relevance
“…The other phenolic acids identified were vanillic, p-coumaric, sinapic, and ferulic acids, with, higher percentage increases of +22.59%, +16.28%, +13.06%, and +5.88%, respectively, registered after thermal processing. There are studies that have reported the caffeic and ferulic acids as main phenolic compounds in oat [60]; vanillic, sinapic, p-coumaric, and protocatechuic acid have been found as well [61,62]. Our findings are in agreement with previously reported phenolic compounds in oat bran [63], being vanillic, p-hydroxybenzoic, ferulic, p-coumaric, caffeic, and sinapic acids.…”
Section: Identification Of Antibacterial Inhibitionsupporting
confidence: 93%
“…The other phenolic acids identified were vanillic, p-coumaric, sinapic, and ferulic acids, with, higher percentage increases of +22.59%, +16.28%, +13.06%, and +5.88%, respectively, registered after thermal processing. There are studies that have reported the caffeic and ferulic acids as main phenolic compounds in oat [60]; vanillic, sinapic, p-coumaric, and protocatechuic acid have been found as well [61,62]. Our findings are in agreement with previously reported phenolic compounds in oat bran [63], being vanillic, p-hydroxybenzoic, ferulic, p-coumaric, caffeic, and sinapic acids.…”
Section: Identification Of Antibacterial Inhibitionsupporting
confidence: 93%
“…These enzymes can decompose the cereal cell walls and release insoluble-bound nutrient substances (Koseki et al 2010). Daniels and Martin (1968) found that most oat phenols are insoluble-bound in oat bran. The increase in TPC in the fermented oat may be due to the activity of these enzymes, which can hydrolyze bound phenols during fermentation.…”
Section: Tpc Of the Tempeh-like Fermented Oatsmentioning
confidence: 99%
“…Glycerides do not commonly occur in plant waxes, but they have been reported before (Martin and Juniper 1970;Herrmann 1978). Esters of caffeic acid with glycerol and m-hydroxy fatty acids have been described by Daniels and Martin (1968). They extracted an ester fraction from peeled oat caryopses containing caffeic acid, ferulic acid, glycerol, and o~-hydroxy fatty acids in molar ratios of about 2: 1 : 1 : 1.…”
Section: Inhibition Of Phenylalanine Ammonia-lyase With Alpmentioning
confidence: 99%